Tugas Manjelis Pengawas Daerah Dalam Melakukan Pengawasan Terhadap Pejabat Umum Notaris - Panarai, Natalia Silfania; Santoso, Budi (Postgraduate Program in Law, Universitas Pattimura, 2024)
Introduction: In the current era of globalization, the presence of Notary services in the development process is increasing. Therefore, in carrying out the position of Notary, it is necessary to supervise and provide guidance so that the Notary can carry out the duties and functions of his position optimally. Supervision and guidance is carried out by the Regional Supervisory Council. However, in its implementation, there are still many Notaries who commit violations both regarding Notarial behavior and the implementation of the Notary's position, apart from that the large area of Malang Regency creates obstacles to the supervision process.Purposes of the Research: Questioning how the Supervision Pattern of the Regional Supervisory Council and whether the supervision of Notaries carried out by the Regional Supervisory Council to Notaries has been carried out effectively.Methods of the Research: This research uses an empirical juridical approach.Results of the Research: The results of this research indicate that the implementation of supervision and guidance by the Regional Supervisory Council has been effective. This can be seen through the supervision pattern carried out by the Regional Supervisory Council, namely by holding regular meetings 1 (one) time every month, providing physical and electronic notifications to notaries, having procedures for handling notaries who are reported by the public, holding internal hearings. Explain the Regional Supervisor to decide on sanctions imposed on Notaries, Provide special rules to Notaries to install CCTV and finger print at the Notary's office in order to minimize violations.